Sink competition and desuckering effects on field performance of triploid and tetraploid plantain genotypes - Tenkouano, A.; Vuylsteke, D.R.; Swennen, Rony L. (Informa UK Limited, 2007)
Reproductive growth in polyarchic Musa spp. varieties occurs by the simultaneous growth of several shoots, resulting in competitive inhibition of fruit development in the individual shoots, particularly under poor soil fertility conditions. Nine plantain genotypes were forced into single-culm growth by continuous sucker removal in the ratoon crop (RC). There were no significant differences among genotypes for days to flowering (DTF) and days to harvest (DTH) in the plant crop (PC), but significant differences occurred in RC for both traits. There was a negative correlation between degree of sucker growth in the PC and DTF or DTH in RC, indicating that early flowering and maturity in the RC occurred as a result of fast sucker development in the PC. Likewise, bunch weight in the RC was positively correlated with sucker growth in the previous crop. However, sucker growth appeared to compete against the development of the bunch in the PC, resulting in a significant reduction in fruit size but not fruit number. Desuckering significantly reduced DTF and DTH in the RC. Bunch weight and fruit size were significantly improved by sucker removal in the RC. Gains were highest for genotypes that normally produce multiple lateral shoots and lowest for those displaying a more hierarchical growth habit. Thus, sucker removal could be recommended as a crop management option for the polyarchic Musa genotypes.